I wanted to understand how velocity changes over time when applying a constant power to a body of mass $m$. I figured out that in this case, since $$P=d/dt(KE)=d/dt(\frac{1}{2}mv^2),$$ integrating I get finally that $v(t)=\sqrt(\frac{2Pt}{m})$. Very easy here.

Now I want to find the same when at the same time a constant power is applied there is an opposite force, like drag $F_d$, that depends on the velocity of the body. Considering air densit $\rho$, drag coefficient $C_d$ and area $A$, in time $t$ that power would be $$P_d(t)=v(t)F_d(t)= (C_d A \frac{\rho}{2}v^2(t))v(t).$$ Since that power depends on the velocity, I cannot just say $P_{net}=P-P_d$ and proceed as before to obtain a speed over time formula. Could anyone provide any insight on this?


2 Answers 2


You will obtain a first-order nonlinear differential equation:

$$P=P-P_d = P-D v^3 = \frac{m}{2} \frac{d}{dt}(v^2) $$

$$\to \frac{d}{dt} (v^2) + \frac{2D}{m} v^3 - \frac{2P}{m} = 0$$

If we define $u(t)=v(t)^2$ , $2D/m = A$ and $-2P/m = B$, we obtain

$$\frac{d}{dt} u(t) + A \ u(t)^{3/2} + B = 0$$

When $A$ is small this reduces to the result you obtained without considering drag.

Sadly though, I don't know any easy way to solve this equation!

  • $\begingroup$ Can easy be simulated :) $\endgroup$ May 16, 2016 at 15:19
  • $\begingroup$ I know, actually I tried first to discretize time and I get reasonable results from that, but I wanted to find a more elegant solution. I'm starting to believe is not possible. Surely is not straightforward, phew!! $\endgroup$ May 16, 2016 at 17:00

'valerio92' is correct and for:

$$\frac{d}{dt} u(t) + A \ u(t)^{3/2} + B = 0$$

... there probably are no analytical solutions (wolfram alpha's DSolve for instance yielded nothing).

But $F_d=C_d A \frac{\rho}{2}v^2$ is not the only model for drag forces. At low speeds:


... can be used, so linear dependence of the drag force on speed.

The differential equation then becomes:


With $A=\frac{2k}{m}$ and $B=-\frac{2P}{m}$.

This solves well: $$-\int \frac{du}{Au+B}=\int dt$$

$$-\frac{1}{A}\ln|Au+B|=t+c$$ Assuming boundary conditions: $$t=0,u=0$$ $$-\frac{1}{A}\ln|B|=c$$ $$\ln|Au+B|=-At+\ln B$$ $$Au+B=e^{-At+\ln B}=Be^{-At}$$ $$u=\frac{B(e^{-At}-1)}{A}$$ Finally, back substituting $u$, $A$ and $B$:


Note that for $t \to +\infty$, then $v=\sqrt{\frac{P}{m}}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.